Multifaceted Role of Rho Proteins in Angiogenesis - Merajver, Sofia D.; Usmani, Saad Z. (Journal of mammary gland biology and neoplasia, 2005)
The Rho family of GTPases is part of the Ras superfamily. The Rho, Rac, and Cdc42 members of the family are present in mammalian cells and have been the subject of attention of researchers due to their vast spectrum of functions. Rac 1, Cdc42, and RhoA are well-known for their role in the regulation of the actin cytoskeleton in promoting the formation of lamellipodia, filopodia, and stress fibers, respectively. The Rho proteins also participate in the control of cell growth, motility, cell-cell adhesions, morphogenesis, cytoskeletal dynamics, and cellular trafficking. The mechanisms for eliciting these functions have become clearer during the last decade. Concordant with their roles in multiple processes of cellular control, the Rho proteins have been shown to be involved in tumor growth, progression, metastasis, and now angiogenesis.